Country role models for development success: The Ghana case - Augustin Kwasi Fosu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
The current paper, first, documents Ghana's 'success' story. Second, it identifies the strategy employed. Third, it provides a brief history of why and how the strategy was adopted. Fourth, it provides some rationale for the success of the strategy, including the roles of domestic and international actors. Fifth, it conjectures the viability of the strategy into the future. Finally, the paper draws lessons for possible application to other less successful countries.
Keywords: O55; 330; role models; Ghana; success; Wirtschaftswachstum; Entwicklung; Wirtschaftspolitik; Ghana